The The Effect of Initial Knowledge and Achievement Motivation on the Learning Result of Narrative Essay Writing in English - Bathesta, Yovi (Universitas Negeri Semarang, 2020)
The objective of this research is to study the effects of the Initial Knowledge in English and the Achievement Motivation in English language on the Learning Result in Narrative Essay Writing in English. The research methodology used is a quasi-experiment with 2 x 2 factorial design which consists of the Initial Knowledge (A) and the Achievement Motivation factors (B) as independent variables, formed from 2 levels (A1, A2) and (B1, B2). The Learning Results are scored by Analytical Rubric (Y1) and Holistic Rubric (Y2) as dependent variables. The analysis of the research is by 1) Descriptive Statistics & Test (Test for Equality of Means) and 2) Multivariate Analysis of Variance. The population is the first semester students of Academic Year 2014-2015 of The London School of Public Relations (LSPR)-Jakarta, while the samples are taken from 2 classes of the lowest and the highest levels of English based on the LSPR English entry test. The Achievement Motivation questionnaires were distributed to the samples, from which 112 respondents' answers were collected. The research concludes that based on the MONOVA, the Initial Knowledge significantly influences the mean scores of the bivariate Analytical Rubric and the Holistic Rubric, while the Achievement Motivation in English doesn’t. And, the factors together, and the interaction between those two factors significantly influences those two bivariate variables.